Utilitarian Ethics In Science: Morality As A Basis Of Scientists' Actions - Ulfah Salwa Hasibuan; Zidna Zidan; Muhammad Nurfaizi Arya Rahardja; Novia, Shinta; Muhamad Parhan (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2024)
This research aims to explain utilitarianism ethics, especially the thoughts of John Stuart Mill in the context of morality as a basis for scientists. Utilitarianism emphasizes action in maximizing happiness and pleasure for many people, in line with what is stated in the Qur’an in surah Ali Isra [17]: 7. Research results from the application of utilitarianism in science emphasize the importance of morality and the responsibility of scientists in ensuring that research results will provide maximum benefits for society. These utilitarian values ​​are in line with the purpose of human creation in the world, namely as God's representatives in providing maximum benefits for society, especially in the fields of Islamic science and thought. In the concept of utilitarianism, there are two figures who played a role in the development of utilitarianism, namely Jeremy Bentham and John Stuart Mill. These two figures worked hand in hand in the development and refinement of the concept of utilitarian ethics. This research is library research. Through a qualitative approach, it is hoped that the results of this research can enrich understanding regarding ethics in science and the contribution that can be made to the welfare of the people.